1993
DOI: 10.1007/bf00229043
|View full text |Cite
|
Sign up to set email alerts
|

Separate populations of visually guided saccades in humans: reaction times and amplitudes

Abstract: The saccadic eye movements of 20 naive adults, 7 naive teenagers, 12 naive children, and 4 trained adult subjects were measured using two single target saccade tasks; the gap and the overlap task. In the gap task, the fixation point was switched off before the target occurred; in the overlap task it remained on until the end of each trial. The target position was randomly selected 4 degrees to the left or 4 degrees to the right of the fixation point. The subjects were instructed to look at the target when it a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
112
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(127 citation statements)
references
References 24 publications
13
112
2
Order By: Relevance
“…Recently Fischer and colleagues (Fischer et al, 1993) have reported a comprehensive study in which target position was random and RT feedback was not provided (as in Experiment 2 of this paper). Thirty-nine naive subjects (20 adults, 7 teenagers, 12 children) and 4 trained adults were tested in the gap and overlap conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Fischer and colleagues (Fischer et al, 1993) have reported a comprehensive study in which target position was random and RT feedback was not provided (as in Experiment 2 of this paper). Thirty-nine naive subjects (20 adults, 7 teenagers, 12 children) and 4 trained adults were tested in the gap and overlap conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Saccade latency was defined as the time interval between target onset and the initiation of a saccadic eye movement. Trials with saccade latency Ͻ100 ms were excluded (0% in this study) because these trials were probably generated not as responses to the visual target (Fischer et al 1993). Trials (0.01%) with saccade latency Ͼ1,000 ms were also excluded in experiment 1.…”
Section: Scoring Of Eye Movement Datamentioning
confidence: 99%
“…The rationale for this classification is threefold. First, sensory-guided (or visually elicited) saccades in no-gap paradigms (old target extinguishes contemporaneously with new target appearance) such as the one used in this study very rarely occur with latencies shorter than 140 ms (Becker, 1989;Fischer et al, 1993). Second, oculomotor studies generally classify saccades with latencies less than 100 ms as predictive because this reflects the minimal time necessary for perceiving a visual stimulus and performing sensorimotor transformations needed to initiate a motor response (Becker, 1989;Wenban-Smith and Findlay, 1991).…”
Section: Statistical Analysesmentioning
confidence: 99%